From man to fly - convergent evidence links FBXO25 to ADHD and comorbid psychiatric phenotypes. - Harich, B.; Klein, M.; Ockeloen, C.W.; van der Voet, M.; Schimmel-Naber, M.; de Leeuw, N.; Schenck, A.; Franke, B. (Journal of Child Psychology and Psychiatry, and Allied Disciplines, 2020)
Mental disorders, including Attention-Deficit/Hyperactivity Disorder (ADHD), have a complex etiology, and identification of underlying genetic risk factors is challenging. This study used a multistep approach to identify and validate a novel risk gene for ADHD and psychiatric comorbidity. In a single family, severely affected by ADHD and cooccurring disorders, we applied single nucleotide polymorphism (SNP)-array analysis to detect copy-number variations (CNVs) linked to disease. Genes present in the identified CNV were subsequently tested for their association with ADHD in the largest data set currently available (n = 55,374); this gene-set and gene-based association analyses were based on common genetic variants. Significant findings were taken forward for functional validation using Drosophila melanogaster as biological model system, altering gene expression using the GAL4-UAS system and a pan-neuronal driver, and subsequently characterizing locomotor activity and sleep as functional readouts. We identified a copy number gain in 8p23.3, which segregated with psychiatric phenotypes in the family and was confirmed by quantitative RT-PCR. Common genetic variants in this locus were associated with ADHD, especially those in FBXO25 and TDRP. Overexpression of the FBXO25 orthologue in two Drosophila models consistently led to increased locomotor activity and reduced sleep compared with the genetic background control. We combine ADHD risk gene identification in an individual family with genetic association testing in a large case-control data set and functional validation in a model system, together providing an important illustration of an integrative approach suggesting that FBXO25 contributes to key features of ADHD and comorbid neuropsychiatric disorders.